Analisis dampak karakter siswa terhadap prestasi belajar siswa kelas IX pada mata pelajaran PPKN di SMP negri 19 kota Jambi: Analisis dampak karakter terhadap prestasi belajar - Prasetyo, Gandung; Usmanto, Heri; Salam, Muhammad (Civic Education Perspective Journal, 2023)
the initial observation, the researcher knew that there were several problems with the number of students' learning achievements that were not good, this was investigated by the researchers because the students' characters were not good in everyday life, so they had poor learning outcomes over time, learning , assignments, and tests done by students. This research method uses qualitative research with descriptive research types. The data collection techniques in this study were in the form of observation, interviews, and documentation. By using research indicators on student character adapted to Civics learning materials. Based on the results of the study, it showed that the impact of poor character was proven by the results of observations, interviews and documentation that the researchers found, this turned out to affect the learning outcomes or student achievement which was not good, caused by a feeling of laziness and irresponsibility, lack of independence and discipline, and underestimating honesty. From this research it can be concluded that the impact of character on student achievement is enormous, the character and morals of children who are not educated properly are caused by various internal and external factors resulting in a decline in character resulting in poor learning achievement among students. .